Timing of Calanus finmarchicus diapause in stochastic environments - Bandara, Kanchana; Varpe, Øystein; Maps, Frédéric; Ji, Rubao; Eiane, Ketil; Tverberg, Vigdis (Ecological Modelling, 2021)
publishedVersion